FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KESELAMATAN BERKENDARA (SAFETY RIDING) PADA PEKERJA - Raisha Octavariny; Delita Hayanti Pajaitan; Anggi Isnani Parinduri; Wilda Wahyuni Siregar (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2021)
Safety riding is riding a motorcycle with behavior give priority to the safety of themselves or other road user. The behavior of one person is influenced by three factors is the predisposition factor (age, work, education, knowledge, and attitude), Enabling factor (driver’s licenses, vehicle condition, and driving items) and Reinforcing factor (regulation and policy, role of coworkers, family support) data Central Bureau of Statistics Republic of North Sumatra Province of 2019 The number of accidents of the accident in North Sumatra reached 6,580 cases of the number increased from the year 2018 amounted to 5,990 cases. The purpose of this research is to know the factors related to the behavior of safety riding on workers. This type of research using the method of analytic approach of cross sectional. As many as 46 respondents research sample and sampling using accidental sampling. The research results obtained amounted to 50% behave safety riding safe and 50% unsafe.Based on data analysis using chi square-related variables are obtained for possession of driver’s licenses (p-value 0,009), vehicle conditions (p-value of 0,000), driving items (p-value 0,000). The advice that can be given is held training and socialization from relate parties about safety riding to raise awareness of workers and workers skills in riding a motorcycle.